Robust effects of predictability across experimental contexts: Evidence from event-related potentials. (November 2019) - Zhang, Wenjia; Chow, Wing-Yee; Liang, Bo; Wang, Suiping
Abstract: Many experiments have shown that comprehenders can generate predictions about upcoming inputs on the fly, but relatively little is known about whether and how comprehenders' sensitivity to predictability may be modulated by the experimental context. The present study used event-related potentials (ERPs) in two experiments to ask whether changing the overall predictive validity of the stimuli will affect comprehenders' brain responses to predictable as well as unpredictable words by manipulating the filler sentences, which made up 50% of the stimuli in each experiment. Contrary to the prediction that predictable words should be processed more easily and elicit a smaller N400 response in a more prediction-encouraging experimental context, we found that participants' N400 response to predictable as well as unpredictable words was smaller when the overall predictive validity of the stimuli was low (that is, when the filler items were incongruous compared to when they were predictable). Further, even though the use of different filler sentences did modulate comprehenders' ERP and behavioural responses, it did not modulate the effect of target word predictability on participants' ERP responses at all. We take the present findings to suggest that healthy young adults' brain responses are inherently sensitive to the predictability of the incoming linguistic stimuli, and that this robust sensitivity can be observed regardless of the make-up of the experimental stimuli. Highlights: We manipulated predictive validity of the stimuli in two ERP experiments. Use of different fillers affected comprehenders' ERP and behavioural responses. Comprehenders' ERPs show the same sensitivity predictability regardless of fillers.